Conceptual model for pluralistic healthcare behaviour: results from a qualitative study in southwestern Uganda. Issue 4 (20th April 2020) - Sundararajan, Radhika; Mwanga-Amumpaire, Juliet; King, Rachel; Ware, Norma C
Abstract : Introduction: Medical pluralism, or concurrent utilisation of multiple therapeutic modalities, is common in various international contexts, and has been characterised as a factor contributing to poor health outcomes in low-resource settings. Traditional healers are ubiquitous providers in most regions, including the study site of southwestern Uganda. Where both informal and formal healthcare services are both available, patients do not engage with both options equally. It is not well understood why patients choose to engage with one healthcare modality over the other. The goal of this study was to explain therapeutic itineraries and create a conceptual framework of pluralistic health behaviour. Methods: In-depth interviews were conducted from September 2017 to February 2018 with patients seeking care at traditional healers (n=30) and at an outpatient medicine clinic (n=30) in Mbarara, Uganda; the study is nested within a longitudinal project examining HIV testing engagement among traditional healer-using communities. Inclusion criteria included age ≥18 years, and ability to provide informed consent. Participants were recruited from practices representing the range of healer specialties. Following an inductive approach, interview transcripts were reviewed and coded to identify conceptual categories explaining healthcare utilisation. Results: We identified three broad categories relevant to healthcare utilisation: (1) traditional healers treat patients with 'care'; (2) biomedicine uses 'modern' technologies and (3) peer 'testimony' influences healthcare engagement. These categories describe variables at the healthcare provider, healthcare system and peer levels that interrelate to motivate individual engagement in pluralistic health resources. Conclusions: Patients perceive clear advantages and disadvantages to biomedical and traditional care in medically pluralistic settings. We identified factors at the healthcare provider, healthcare system and peer levels which influence patients' therapeutic itineraries. Our findings provide a basis to improve health outcomes in medically pluralistic settings, and underscore the importance of recognising traditional healers as important stakeholders in community health.